Peran Tradisi Pesantren dalam Membentuk Akhlak Santri (Studi Kasus Santri Pondok Pesantren Al-Falah, Kecamatan Silo, Kabupaten Jember): The Role of Pesantren Tradition in Fostering Santri Morals (Case Study of Santri Al-Falah, Silo Jember District) - Fitriyatul Hanifiyah (Prodi PAI, Fakultas Tarbiyah, UNIDA GONTORs Tarbiyah, Universitas Darussalam Gontor, 2024)
Morals are an important element in the life of a student. To shape the morals or attitudes of a student into commendable morals and in accordance with the predicate of santri, it is necessary to foster familiarization with the traditions of pesantren. Pesantren institutions have certain traditions that are applied in the pesantren environment, as well as in the Al-Falah Islamic boarding school foundation, which requires its students to follow the traditions that have prevailed in the pesantren environment. This research focuses on the implementation and habituation of pesantren traditions that must be followed in order to build and mold the morals of students into commendable morals. Data collection in this study used non-participant observation, in-depth interviews, and documentation. The data analysis technique starts with data collection, data reduction, data presentation, and conclusions. In checking the validity of the data using source triangulation, The results of this study show a change in the morals of students for the better by showing an attitude of trust. The supporting factors are the discipline of the management, the foundation, and good collaboration in controlling, while the inhibiting factor is the character or innate character inherent in the behavior of students.